FAKTOR-FAKTOR YANG MEMPENGARUHI KETEPATAN WAKTU PELAPORAN KEUANGAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR PADA BURSA EFEK INDONESIA PERIODE 2005-2007 - Ken Midansih; Wibowo Wibowo (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2011)
The purpose of this research is to analyze factors that influenced the timeliness of financial report on manufacture companies listed in the Indonesian Stock Exchange. The dependent variable that used in this research are timeliness of financial reporting to BAPEPAM, timeliness completion of audit and timeliness publication in mass media and variable independent are profitability, financial leverage, liquidity, firms size, public ownership, reputation of public accountant firm, auditor opinion, and information communication technology. The population to be examined in this study were 156 manufacture companies. The result of examination to 52 companies for the period of 2005-2007 listed in the Indonesian Stock Exchange which have been selected using purposive sampling method. Data to be used in the study was secondary data. The analysis method of data in this research is regression logistic. The result of this research found that profitability, financial leverage, liquidity, firms size, shareholder's dispersion, reputation ofpublic accountant firm, auditor opinion, and information communication technology significantly affect timeliness of financial reporting to BAPEPAM. On the other hands, profitability, financial leverage, liquidity, firms size, shareholder's dispersion, reputation ofpublic accountant firm, auditor opinion, and information communication technology were not significantly affect timeliness completion of audit and publication in mass media.